The MASCC Textbook of Cancer Supportive Care and Survivorship (Springer International Publishing, 2018)
This book is intended for medical students, residents, and fellows, as well as medical oncologists, radiation oncologists, surgeons, general practitioners, nurses and allied health workers. Complete with case vignettes, key points, and sidebar summaries to further assist readers using practical tips and tricks, this textbook provides current, updated information on the management and prevention of cancer-related side effects, referring to up-to-date sources that are useful for conducting further research. It also introduces new topics, such as financial toxicity and complementary medicine, as well as covering the new side effects of targeted therapies not covered in the last edition. Additionally, MASCC Textbook of Cancer Supportive Care and Survivorship, 2nd edition assembles international, multidisciplinary experts who focus on a comprehensive range of symptoms and side effects associated with cancer and its treatment. .